2015
DOI: 10.1186/s13287-015-0240-9
|View full text |Cite
|
Sign up to set email alerts
|

The challenges and promises of allogeneic mesenchymal stem cells for use as a cell-based therapy

Abstract: Mesenchymal stem cells (MSCs) are ideal for cell-based therapy in various inflammatory diseases because of their immunosuppressive and tissue repair properties. Moreover, their immunosuppressive properties and low immunogenicity contribute to a reduced or weakened immune response elicited by the implantation of allogeneic MSCs compared with other cell types. Therefore, implantation of allogeneic MSCs may be a promising cell-based therapy. In this review, we first summarize the unique advantages of allogeneic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
216
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(230 citation statements)
references
References 74 publications
(71 reference statements)
3
216
0
2
Order By: Relevance
“…Many studies have shown that MSCs can either increase the number and function of Tregs or promote the conversion of naive CD4 + T cells into Tregs (Takahashi et al 2014. MSCs possess low immunogenicity (Zhang et al 2015). The anti-inflammatory and immunosuppressed properties of MSCs in the periapical area may also contribute to tissue regeneration and wound healing (Zhang et al 2013, Araujo-Pires et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that MSCs can either increase the number and function of Tregs or promote the conversion of naive CD4 + T cells into Tregs (Takahashi et al 2014. MSCs possess low immunogenicity (Zhang et al 2015). The anti-inflammatory and immunosuppressed properties of MSCs in the periapical area may also contribute to tissue regeneration and wound healing (Zhang et al 2013, Araujo-Pires et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…78 It has a great potential of regenerative medicine due to its ability and immunomodulatory characteristic. 79 The modulation of MSC local environment for repair and regeneration is modulated by the direct cell to cell interaction or secretion of immune-related molecules. 66 However, in previous studied, MSC is found to play roles in facilitating tumorigenesis and cancer.…”
Section: Stem Cells Versus Tumor Cellsmentioning
confidence: 99%
“…MSCs are a promising cell type for therapy, because they have the potential to differentiate into repair tissue and also have trophic and immunomodulatory capacities. While they have been shown to be capable of improving damaged tissue, their contribution does not seem to originate from long-term engraftment and differentiation (Toma et al, 2002;Zhang et al, 2015). This suggests that MSCs can also stimulate endogenous tissue repair, in addition to their ability to differentiate into cells of the mesoderm lineage.…”
Section: Introductionmentioning
confidence: 98%